Analysis of the Impact of Verbal Bullying on Elementary School Children - Kurniati, Novi; Purnamasari, Iin; Rahmawati, Intan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Education is a process, method or act of educating. Education aims to change a person's behavior or attitude by shaping the attitude or behavior of that person. The purpose of this study was to find out the teacher's knowledge about verbal bullying, identify various forms of verbal bullying and the behavior shown by perpetrators, victims and spectators of verbal bullying that occurred at SD Negeri Pulosari 01, Karangtengah District, Demak Regency. This type of research is qualitative research. The method in this study uses observation techniques, interviews and documentation. From the findings of this study indicate that verbal bullying is when someone uses aggressive spoken language that is done with the intention of demeaning, slandering, and embarrassing. Bullying of students during empty class hours, recess time, or during school hours. Victims and perpetrators can suffer the negative effects of verbal bullying. The impact on victims is 1) Psychological Problems; 2) Sleep Disorders; 3) Unable to socialize; 4) decreased learning outcomes. While the impact on the perpetrator is getting punished. Some things students need to do when they see verbal bullying are 1) Don't be intimidated; 2) Report to adults; 3) Reprimand the perpetrators of bullying; and 4) Accompany the victim. Suggestions in this study are cooperation between the school and parents of students in optimizing the prevention of verbal bullying behavior. Parents can convey the bullying they are experiencing, and schools open up opportunities to discuss finding the best solution.